Editorial: Resilience Resources in Chronic Pain Patients: The Path to Adaptation. - Ramírez-Maestre, María del Carmen; De la Vega, Rocío; Sturgeon, John Andrew; Peters, Madelon L. (Frontiers, 2019)
Editorial on the Research Topic: - Resilience Resources in Chronic Pain Patients: The Path to Adaptation
Keywords: Dolor crónico - Aspectos psicológicos; Resiliencia (Psicología); Chronic pain; Resilient resources; Adaptation; Wellbeing; Positive psychology